2011
DOI: 10.1116/1.3520433
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vacuum ultraviolet and ultraviolet irradiation on mobile charges in the bandgap of low-k-porous organosilicate dielectrics

Abstract: Capacitance-voltage ͑C-V͒ measurements are used to determine the effect of vacuum ultraviolet ͑VUV͒ and ultraviolet irradiation on mobile charges in porous low-k organosilicate ͑SiCOH͒ dielectrics. Hysteresis in the C-V characteristics shows that VUV irradiation increases the number of mobile charges in the dielectric. This is because VUV photons excite the trapped electrons from defect states to make them mobile carriers. Conversely UV reverses this effect by reducing the mobile charges through photoemission … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…12,13 Specific electrical reliability concerns for low-and high-k dielectrics include line-line interconnect 14,15 and gate dielectric leakage, 16,17 dielectric breakdown (V bd ), [18][19][20] time-dependent dielectric breakdown, [21][22][23][24] stress-induced leakage currents, 25,26 bias temperature instabilities, 27,28 charge trapping, [29][30][31][32] and a host of other charge-related buildup phenomena. 33,34 Despite the wide range of reliability concerns, a key ingredient in the models for all of these phenomena is some type of "defect" or "trap" in the dielectric material. [35][36][37][38][39][40][41][42][43][44][45] Tremendous resources and effort have been devoted to detecting and identifying the chemical identity and physical structure of such defects and traps in SiO 2 , [46][47][48] and they continue to be the subject of significant research interest.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Specific electrical reliability concerns for low-and high-k dielectrics include line-line interconnect 14,15 and gate dielectric leakage, 16,17 dielectric breakdown (V bd ), [18][19][20] time-dependent dielectric breakdown, [21][22][23][24] stress-induced leakage currents, 25,26 bias temperature instabilities, 27,28 charge trapping, [29][30][31][32] and a host of other charge-related buildup phenomena. 33,34 Despite the wide range of reliability concerns, a key ingredient in the models for all of these phenomena is some type of "defect" or "trap" in the dielectric material. [35][36][37][38][39][40][41][42][43][44][45] Tremendous resources and effort have been devoted to detecting and identifying the chemical identity and physical structure of such defects and traps in SiO 2 , [46][47][48] and they continue to be the subject of significant research interest.…”
Section: Introductionmentioning
confidence: 99%
“…1,7 For low-k materials, it has been additionally shown that electrical traps and defects can be created by downstream porogen removal and plasma etching processes that expose the low-k material to intense UV-VUV radiation, energetic ions, and chemically active radicals. [17][18][19][20][21][22][23] Further studies have shown a direct correlation between trap/defect densities, leakage currents and TDDB failures. 18,24 Unfortunately, the current understanding of the chemical identity, structure, and energy level of electrical traps and defects in low-k materials is still limited.…”
mentioning
confidence: 97%
“…[19][20][21] When a VUV photon is incident on a dielectric surface, there are several processes that can occur depending on the thickness of the dielectric layer and the energy of the VUV photon. 22 If there is an electric field within the dielectric layer, the free electrons and holes can move in response to the electric field until they become trapped, recombine, or leave the dielectric. The location of the electron-hole pairs that are generated within the dielectric depends on the penetration depth of the VUV photons ($10 nm for SiO 2 ).…”
Section: Introductionmentioning
confidence: 99%